International trade, foreign investment, and the environment - Michael Rauscher (Universität Rostock, Institut für Volkswirtschaftslehre, 2001)
This paper surveys the literature on the relationship between international trade in goods and the factors and the environment. Traditional approaches based on the HEckscher-Ohlin trade model and more recent models looking at non-competetive market structures are discussed. Moreover, the paper covers intertemporal aspects (foreign debt, stock pollutants), public-choice models (the political economy), the empirical evidence and the instituonal issues. This paper was written for the Handbook of Environmental and Resource Economics to be edited by Jeffrey Vincent and Karl-Göran Mäler for the Handbooks in Economics series (North-Holland, Amsterdam), where a revised and probably shorter version of it will appear. Comments are very welcome.
Keywords: 330; Außenwirtschaftstheorie; Neue Außenhandelstheorie; Umweltökonomik; Umweltpolitik; Außenhandelspolitik; Direktinvestition; Strategische Handelspolitik; Intertemporale Allokation; Umweltschutz; Theorie; Welt